(untitled) (Eastern Medical College Journal, 2023)
Background:Colorectal carcinoma is one of the most common and leading causes of cancer-related death in the United States. Fecal occult blood test used as a screening test followed by sigmoidoscopy or colonoscopy to early detection of colorectal carcinoma. Objective: To assess the fecal occult blood by fecal occult blood test of the patients who fulfill the criteria as a screening for colorectal carcinoma and evaluation of those patients who are positive for fecal occult blood test for early detection of colorectal carcinoma by fiber optic full colonoscopy. Materials and Methods:This hospital based observational study was carried out in Dhaka Medical College Hospital, Dhaka, Bangladesh for a period of 6 month from July 2009 to December 2009. A total of 50 cases were selected by convenient sampling fulfilling the inclusion and exclusion criteria. Those who had positive fecal occult blood test were further advised for fiber optic full colonoscopy and biopsies were taken where necessary as a screening for colorectal carcinoma.Reported results and relevant data were recorded in the data sheet and then analyzed by standard statistical method. Results: Total number of cases was 50. Adequate samples were obtained in 46 (92%) cases, among the adequate samples 18 (36%) were malignant and 28 (56%) were benign or nonmalignant lesions. Among the benign lesions, nonspecific colitis (13;26%) was the most common followed by rectal polyp (1;2%), proctocolitis (1;2%) and Normal tissue (1:2%). Adenocarcinoma (18;36%) was the most common type of colorectal carcinoma. In male, colorectal carcinoma (15;30%) was the more common than female (3;6%). Conclusion: Guaiac based FOBT is a simple and less expensive test for identification of occult blood in stool. It is easily done with minimum cost and suitable test as a screening for early diagnosis of colorectal cancer. FOBT positive patient’s fiber optic colonoscopy is a wonderful investigation for further diagnosing the colonic lesion. Eastern Med Coll J. July 2023; 8 (2):48-53